Disfunção temporomandibular e sua associação com a qualidade de vida - Trize, Débora de Melo (2015)
The aim of this study was to determine the impact of Temporomandibular Disorders (TMD) in Quality of Life (QL) of 102 volunteer patients (68 female and 34 male) aged 19 to 86 years, that seeking medical care in health clinics at Sagrado Coração University (USC), in the period from September to December 2013. The subjects were examined following the Research Criteria for Temporomandibular Disorders (RDC/TMD), using a mechanical algometer (Palpeter) with standardized pressure of 0.5 and 1.0 kg, and SF-36 questionnaire for assessing QL Data were tabulated for statistical analysis and the variables related were correlated with the clinical findings of the TMD and QL. Fifity percent of the patients were positive for TMD, 39.2% among those classified as myofascial pain group. The TMD group was significantly associated with uncomfortable bite (p = 0.0000), temporomandibular joint (TMJ) clicking (p = 0.0001) and gnashing of teeth (p = 0.0001). SF-36 questionnaire revealed that the domains of pain (mean score of 47.80%) (p <0.0001) and mental health 62.67% (p <0.05), were strongly associated with TMD according to Mann Whitney test. During clinical examination, some adaptations had to be made, considering the influence of patient manipulation. Also, special attention was taken when pplying SF-36 due to socio-cultural level of the patients. It was concluded that the QL of individuals, mostly women, with TMD was mainly negatively affected by the presence of pain and change mental health. It is emphazised that the lack of a careful explanation of SF-36 for patients better understanding, as well as a proper manipulation of the patients during clinical examination can directly interfere in the diagnosis and analysis of TMD s impact on their QL